Understanding the Dynamics of Transition of the Women’s Movement in Armenia: Challenges for Democratic Representation and Increasing Political Influence - Olga Azatyan (Journal of Political Science: Bulletin of Yerevan University)
The article analyzes the origins of women’s social movements in the transit Armenian NGO network, which are closely linked to the emergence of modernity, where capitalism, state-building, urbanization and other factors created conditions for collective action. The results of women's civic initiatives are divided into direct results, such as changes in public policy, and indirect results, such as shifts in public opinion. The article draws attention to the fact that women's movements in Armenia are distinguished by the fact that they are future-oriented, ideologically driven and more inclusive than other civic initiatives. These new movements are often devoid of hierarchical structures, advocate for horizontal cooperation and are often marginalized by the media and public opinion. In this sense, the aim of this article is to analyze the resilience of women's movements in Armenia using the theory of civil society and political transformation of post-Soviet countries, focusing on the quality of political institutions and regimes, mobilizing social networks and protest cycles. The theoretical and practical position of this article reveals the peculiarities of the development and effective political adaptation of the women's community in the context of European integration of Armenian society. The main provisions of this article contribute to further research into the problems of women’s political adaptation in a transitional economy, identifying the main directions for establishing gender equality as one of the priorities of public policy, as well as strengthening the political activism of women in Armenia.